2014
DOI: 10.1007/s13762-014-0555-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic remediation of perchloroethylene-contaminated soil

Abstract: One large group of persistent and toxic contaminants is the hydrophobic organic contaminants. Among them, perchloroethylene (PCE) has been recognized as a representative group of these pollutants with low solubility. This study reports on the effects of electrokinetic remediation with non-ionic surfactant on PCEcontaminated soil. The performance of electrokinetic process was investigated in the treatment of clay soil that artificially contaminated with two levels: 10,000 and 30,000 mg/kg PCE and 0.33 g/kg Trit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In addition, due to the limited proton transfer in the soil, the sediment pH has increased from the anode compartment region to the cathode one [5]. Similar results are obtained in all soil remediation by electrokinetic method [26]. It can be concluded that pH variation is affected by two important mechanisms; electro-osmosis transfer along with electromigration.…”
Section: Ph Variationsupporting
confidence: 64%
“…In addition, due to the limited proton transfer in the soil, the sediment pH has increased from the anode compartment region to the cathode one [5]. Similar results are obtained in all soil remediation by electrokinetic method [26]. It can be concluded that pH variation is affected by two important mechanisms; electro-osmosis transfer along with electromigration.…”
Section: Ph Variationsupporting
confidence: 64%
“…The transport of the predominantly neutral PFASs can be possibly explained by the electro-osmotic flow. Similarly, previous studies have reported trends towards the cathode for neutral organic contaminants, e.g., petroleum hydrocarbons (Lee et al, 2016), trichloroethylene (Chung and Lee, 2007), 2,4,6-trichlorophenol (Ruiz et al, 2014 and perchloroethylene (Gholami et al, 2014), and have attributed these to extraction from soil due to electro-osmotic flow. Hence, electro-remediation of soil can be applied for both charged and neutral PFASs, which can be retrieved at opposing electrodes.…”
Section: Performance Parameters Of the Electrodialytic Experimentsmentioning
confidence: 54%
“…For example, the acid dissociation constant (pKa) value of perfluoroalkyl carboxylates (PFCAs) and perfluoroalkane sulfonates (PFSAs) is generally <2 (Du et al, 2014;, which makes PFASs ideal candidates for electromigration. This is in contrast to most other regulated persistent organic pollutants of concern for soil remediation, which most are neutral under environmental pH (Ren et al, 2018) and therefore not subjectable to electromigration (Chung and Lee, 2007;Ruiz et al, 2014;Gholami et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…The use of an electrokinetic (EK) process in soil remediation has received increasing attention worldwide because of its unique applicability to low-permeability soils (Khodadadi et al, 2011;Gholami and Yousefi Kebria, 2012).…”
Section: Introductionmentioning
confidence: 99%